2018
DOI: 10.1007/s10068-018-0393-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of alginate and gelatin-based edible coating materials as alternatives to traditional coating for improving the quality of pastirma

Abstract: This research was conducted to study the efficacy of sodium alginate and gelatin coating materials in improving the quality of pastirma. Pastirma was coated with traditional, alginate or gelatin coatings, stored at 4°C for 4 weeks and examined weekly. Alginate and gelatin coated-pastirma revealed lower TBARS values which was within the acceptable limit (0.67 and 0.86 mg/kg) until the end of storage, however, the TBARS values of traditionally coated pastirma reached 1.33 by the end of storage. Edible coating de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
2
12
0
1
Order By: Relevance
“…This lowered rate was attributed to the antioxidant activity of AEO. Similar to the present study, increasing trend for TBARS has been observed in many studies when employing biopolymers for preservation of meats (Abdallah et al., 2018; Abdollahi et al., 2014; Azlin-Hasim et al., 2015; Farajzadeh et al., 2016; Hassanzadeh et al., 2017; Sun et al., 2019). Nevertheless, in some researches an irregular TBARS trend was reported during chilled storage of fresh meats (Andevari and Rezaei, 2011; Bazargani-Gilani et al., 2015; Hosseini et al., 2016).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…This lowered rate was attributed to the antioxidant activity of AEO. Similar to the present study, increasing trend for TBARS has been observed in many studies when employing biopolymers for preservation of meats (Abdallah et al., 2018; Abdollahi et al., 2014; Azlin-Hasim et al., 2015; Farajzadeh et al., 2016; Hassanzadeh et al., 2017; Sun et al., 2019). Nevertheless, in some researches an irregular TBARS trend was reported during chilled storage of fresh meats (Andevari and Rezaei, 2011; Bazargani-Gilani et al., 2015; Hosseini et al., 2016).…”
Section: Resultssupporting
confidence: 90%
“…Similar to the present study, the inability of gelatin coating for controlling the surface microbial growth during refrigerated storage has been reported (Andevari and Rezaei, 2011; Hosseini et al, 2016). In contrast, Abdallah et al (2018) observed that the gelatin-alginate coating lowered the aerobic bacteria and mold growth on pastirma by means of the limitation of oxygen diffusion. Moreover, antimicrobial effect of the gelatin film making solution on Listeria monocytogenes was confirmed in one study (Nowzari et al, 2013).…”
Section: Microbial Assessmentssupporting
confidence: 89%
See 3 more Smart Citations